As formas camín e chen en galego e asturiano: solucións supra-rexionais, solucións rexionais e contínuum xeolectal - DUBERT GARCÍA, Francisco (Revista de Filología Románica, 2010)
This work tries to show the problems that emerge by classifying the dialectal features shared by most than one language as pertaining only to one. In order to reach this goal, the romance results of the latin groups -INU and -ENU in the northwest of the Iberian Peninsula will be analysed from a geolinguistic point of view. The notions of supra-regional and regional solutions, taken from Diego Catalán (1956-57/1957- 58), as well as the notion of geolectal continuum, will be used to overcome these problems. A common kind of evolution for -INU and -ENU will be defended to speeches that can be considered Asturian and to speeches that can be considered Galician; this common evolution was probably spread by diffusion processes. Finally, the inconvenience of saying that in Galician there exist Asturian features or that in Asturian there exist Galician features will be shown.